Effect of nanosilver on the photodegradation of poly(lactic acid). Issue 8 (14th November 2013) - Mucha, Maria; Bialas, Sylwia; Kaczmarek, Halina
ABSTRACT The poly(lactic acid), PLA, mixed with nanosilver in solution easily forms nanocomposite in solid state (after solvent evaporation), which was proved by UV–Vis spectroscopy. This work focuses on photodegradation occurring in PLA films doped with nanosilver. The changes in chemical structure of photodegraded PLA has been determined using FTIR spectroscopy. Differential scanning calorimetry of UV‐irradiated PLA samples provided information on polymer glass transition and crystallization/melting processes. It was found that PLA alone is more sensitive to photodegradation than PLA/silver nanocomposites. The mechanism of nanocomposite photodegradation and effect of nanosilver was discussed. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40144.